The influence of COVID-19 on the incidence and antimicrobial resistance of multi-drug resistant Klebsiella pneumoniae, Pseudomonas aeruginosa and Acinetobacter baumannii in a tertiary care hospital in Belgrade (Serbia) - Predrag Savic; Milos Gostimirovic; Teodora Vitorovic; Jovana Rajkovic; Ana Bukarica; Ljiljana Gojkovic-Bukarica (Journal of Global Antimicrobial Resistance)
BACKGROUND: Coronavirus pandemic (COVID-19) affected antimicrobial stewardship and increased antimicrobial resistance (MDR) of common nosocomial pathogens. Main reasons for this were frequent and uncritical use of antibiotics, regardless of whether the bacterial infection was proven or not, ''off-label'' use of antibiotics (e.g viral pneumonia), prolonged hospital stay and outpatient self-administration. Here we analysed how COVID-19 pandemic influenced the incidence and resistance rate of Klebsiella pneumoniae (KPN), Pseudomonas aeruginosa (PAE) and Acinetobacter baumannii (ABA) isolated from blood samples in a tertiary care hospital in Belgrade (Serbia), between 1, April 2019 and 1 April, 2022. METHODS: Identification and susceptibility testing were performed using the Vitek 2 system. The burden of resistance for each antibiotic was calculated as the percentage of all ‘’resistant’’ + ‘’intermediate resistant’’ results among tested isolates from all patients samples. For analysis of susceptibility rates we used the WHONET 5.6 software. RESULTS: Total numbers of all bacterial isolates were 3286, 2685 and 3064, respectively. Out of them, total number of isolates of KPN were 290 (8.8%), 247 (9.2%) and 275 (9%), of PAE were 177 (5.4%), 103 (3.8%) and 104 (6.4%) and of ABA were 144 (4.4%), 323 (12%) and 337 (11%), recpectively. Compared with 2019, KPN showed statistically significant trend of increasing resistance (p<0.001) after pandemic, mostly with meropenem (65.2%), ciprofloxacin (87.6%) and colistin (40.5%). CONCLUSIONS: COVID-19 might have caused increased prevalence and MDR of common pathogens, especially of KPN, which is probably due to the high percent of patients on the mechanical ventilation and prolonged hospital stay.